The Impact of Obesity and Hypertension History on Preeclampsia During Pregnancy - Arni Kurniasari; Wilis Dwi Pangesti (LPPM Universitas Harapan Bangsa, 2024)
Preeclampsia is the leading cause of maternal mortality and a serious pregnancy complication. Hypertension and obesity in pregnant women are significant risk factors for preeclampsia. This study examined the impact of obesity and high blood pressure history on preeclampsia risk and onset. This quantitative case-control study utilized secondary data from medical records at RSUD Prof. Dr. Margono Soekarjo. A purposive sampling technique selected 314 respondents, with 157 in the case group and 157 in the control group. Data analysis used chi-square tests. The result revealed that obesity (p-value = 0.001, OR = 8.3) and hypertension history (p-value = 0.001, OR = 13.6) were significant risk factors for preeclampsia. However, obesity and hypertension did not affect preeclampsia onset differently. These conditions can lead to endothelial dysfunction and organ damage, increasing preeclampsia risk in pregnant women.